БОЛАЛАР СОҒЛОМЛАШТИРИШ ОРОМГОҲЛАРИДА КИЧИК МАКТАБ ЁШИДАГИ ЎҚУВЧИЛАРНИНГ МАЪНАВИЙ-АХЛОҚИЙ ФАЗИЛАТЛАРИНИ ШАКЛЛАНТИРИШНИНГ КОНЦЕПТУАЛ, ИЖТИМОИЙ, ҲУҚУҚИЙ АСОСЛАРИ - Айназарова, А.Ж. (SCIENCE and SOCIETY, 2020)
The article describes the conceptual, social, legal basis for the formation of spiritual and moral qualities of primary school students in children’s health camps from a scientific and practical point of view. It is also theoretically illustrated that the formation of spiritual and moral qualities of children is easy and effective, if the basis of the upbringing of spiritual and moral qualities is formed on the basis of adherence to national values, a healthy worldview and moral norms.